Managing lorlatinib-induced weight gain through a structured exercise intervention in an ALK+ NSCLC patient: a case report - Ciurnelli, Christian; Mariangela Scaglione, Ilaria; Eccher, Serena; Borsati, Anita; Toniolo, Linda; Adamoli, Gloria; Tregnago, Daniela; Longo, Lucia; Sposito, Marco; Insolda, Jessica; Milella, Michele; Schena, Federico; et al. (Frontiers in Oncology, 2025)
BackgroundIn non-small cell lung cancer (NSCLC), ALK tyrosine kinase inhibitors (TKIs) have been associated with significant weight gain, predominantly in fat tissues. To date, only one case report has evaluated the impact of pharmacologic intervention on managing this drug-related side effect, with concerns about potential interactions with oncological treatments. No information is available regarding non-pharmacological intervention.Case descriptionA 43-year-old man affected by metastatic ALK-rearranged NSCLC developed Grade 1 weight gain 1.5 months after starting Lorlatinib. The patient participated in a structured exercise program to manage this side effect. The program lasted 6 months and consisted of aerobic activities, including continuous and interval training, as well as resistance exercises using body weight/isotonic machines, performed at moderate to somewhat vigorous intensity, twice a week. Assessments were performed at three and six months, and included physical fitness and patient-reported outcomes parameters. Although the weight remained stable, body composition analysis, via bioimpedance and CT scan, revealed a decrease in fat tissue and an increase in muscle mass. Moreover, the patient reported improvements in physical fitness, especially in cardiorespiratory fitness, muscle strength, endurance, and flexibility. Among the patient-reported outcomes, different domains of quality of life improved.ConclusionThis case may represent the backbone for further interventional studies aimed at determining the real efficacy of exercise intervention in preventing or controlling weight gain in this population.